Indigenous Cities : Urban Indian Fiction and the Histories of Relocation - Furlan, Laura M. (Book collections on Project MUSE., 2017)
"A critical study of contemporary American Indian narratives set in urban spaces that reveals how these texts respond to diaspora, dislocation, citizenship, and reclamation"--